Enhanced trans‐to‐cis photoisomerization quantum yield of azobenzene spatially confined in silver nanoparticle aggregates. (5th February 2020) - Sun, Lili; Wang, Changshun; Pan, Yujia; Chen, Tianyu; Lv, Ziyao
Abstract: Photoisomerization of azobenzene spatially confined in silver nanoparticle (AgNP) aggregates and in ethanol solution was monitored by Raman spectroscopy inside optically clear colorimetric dishes. After ultraviolet irradiation, overall Raman intensity assigned to trans‐azobenzene of these two samples decreased, and notably, a cis peak appeared at 599 cm −1, assigned to C─N═N─C torsional mode. The Raman intensity at 1, 007 cm −1, assigned to trans‐azobenzene, was recorded versus irradiation time for analyzing the trans‐to‐cis photoisomerization quantum yield (PQY). By combining our theoretical derivation and standard curve of Raman spectra, the trans‐to‐cis PQY of azobenzene in AgNP aggregates was roughly calculated to be 79.0% higher than that in ethanol solution. The enhancement mechanism was discussed in terms of the competition between enhanced local optical field from surface plasmon resonance and the accelerated nonradiative decay of excited azobenzene molecules together. Abstract : The Raman spectra of the irradiated azobenzene showed a cis signature peak at 599 cm −1 both in silver nanoparticle (AgNP) aggregates and ethanol solution. Trans‐to‐cis photoisomerization quantum yield (PQY) of azobenzene in AgNP aggregates was roughly calculated to be 79.0% higher than that in ethanol solution. Raman spectra here played an important role in calculating the quantitative value of the change of PQY.